Transient poverty, poverty dynamics, and vulnerability to poverty An empirical analysis using a balanced panel from rural China - Ward, Patrick S (World development, 2016)
China's economic reforms starting in the late 1970s have resulted in rapid economic growth, with annual growth in gross domestic product averaging greater than 10 percent per year for more than thirty years. Accompanying this rapid growth in national accounts have been rapid and widespread reductions in poverty. With these reductions in poverty, however, there has often been observed an increase in income inequality, both between as well as within rural and urban sectors. This rising income gap challenges the notion that economic reforms in China have been as successful as the poverty statistics would suggest. In this paper, we suggest that an alternative view would be to consider the effects of these reforms on changing the chronic nature of poverty and reducing household vulnerability to poverty. Using a balanced panel from rural China from 1991 through 2006, we find that most poverty among our sample has shifted from being chronic in nature to being transient, with households either shifting into a state of being non-poor moving in and out of poverty. Among our sample, vulnerability to poverty has been declining over time, but the declines are not uniform over time or space. We decompose household vulnerability status into two proximate causes: low expected income and high income variability, finding vulnerability increasingly due to income variability. Additionally, we demonstrate that vulnerable households have very different characteristics than non-vulnerable households